Mingle Music Technique: Boosting Students’ Speaking Ability - Ilinawati; Sijono (Proceedings of the International Conference on Literacy and Education, 2020)
The main focus of this study is boosting students’ speaking ability by using mingle music technique. The data were taken from the second semester students of English Language Study program of STKIP PersadaKhatulistiwaSintang , in Academic Year 2018/2019 which consisted of 22 students. A classroom action research design was employed in this research. In collecting the data, researchers used observation checklist, field note, interview and students’ oral performance test. The research was conducted in two cycles, where in each cycle consisted of 1 meeting. It took 150 minutes for 3sks.The result showed that the students’ involvement in teaching learning process improved from 80, 36 % in cycle 1 to 90,00 % in cycle two. It can be concluded that the implementation of mingle music technique succeeded boosting students’ speaking ability.